Immunosuppressive potential evaluation of synovial fluid mesenchymal stem cells grown on 3D scaffolds as an alternative source of MSCs for osteoarthritis cartilage studies - Paradiso, Francesca; Lenna, Stefania; Isbell, Reagan; Garcia Garza, Maria Fernanda; Williams, Michael; Varner, Catherine; Mcculloch, Patrick; Taraballi, Francesca (Frontiers in Biomaterials Science, 2022)
Osteoarthritis (OA) is a chronic degenerative joint disease that will continue to impose an increasing burden on the aging population unless disease-modifying therapies are developed. OA is the leading cause of disability in older adults and leads to pain, reduced mobility, and decreased quality of life. Mesenchymal stem cells (MSC) - based therapies offer a potential regenerative solution given their ability to differentiate to all tissues within a joint and moreover, to modulate the local inflammatory response. Determining the ideal MSC source, processing, and delivery vehicle are further challenges that must be addressed to optimize biologics-based treatment of OA. Although bone marrow-derived mesenchymal stem cells (BM-MSCs) represent the gold standard in cell therapies for OA, synovial fluid-derived stem cells (SF-MSCs) can be a less invasive, promising alternative. They can be easily harvested during arthrocentesis, arthroscopy or open knee surgery with a minimally invasive act allowing personalized autologous therapies. SF-MSCs isolated from human synovial fluid of patients suffering from advanced OA retained stemness markers and inflammatory potential in 2D culture condition showing similar morphology and clonogenicity potential compared to BM-MSCs. To further boost their immunomodulatory properties, we coupled SF-MSCs with a biomimetic scaffold made of collagen and chondroitin sulfate (CL CS), previously reported as immune-tuning materials. The 3D culture further promoted immunosuppressive marker expression in SF-MSCs compared to 2D culture. Although scaffold-free injection of MSCs predominates in ongoing clinical trials, biomatrices may prove a critical adjuvant as these therapies evolve. A combination of SF-MSCs and 3D CL CS biomimetic scaffolds could represent a potential disease-modifying therapy necessary to stem the tide of OA.